Two New Species of Euscorpius (Scorpiones, Euscorpiidae) from Bulgaria and Greece - Tropea, G.; Fet, V.; Parmakelis, A.; Stathi, I. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
Two scorpion species, Euscorpius petarberoni sp. n. (Bulgaria) and E. trichasi sp. n. (Greece), are described based on morphological and molecular evidence; E. petarberoni sp. n. is related to E. popovi Tropea et al., 2015, E. drenskii Tropea et al., 2015, and E. thracicus Kovařík et al., 2020, while E. trichasi sp. n. is related to E. kabateki Kovařík & Šťáhlavský, 2020.